Adaptive system of controlling temperature mode of polymer materials extrusion - Жученко, Олексій (Eastern-European Journal of Enterprise Technologies, 2014)
An adaptive system of controlling the temperature mode of an extruder under normal operation conditions is presented. The analysis concerning the importance of maintaining the given temperature of the extruder when manufacturing polymer materials was carried out. The necessity in applying the principle of adaptation while conducting the process was substantiated. As a controlling object, a single-screw three-zone extruder was used. As a model, the autoregressive-moving average model was proposed. The results of studying the adaptive control system with different methods of identifying the model parameters, basing on the recursive methods of least squares and their modifications, were given. The synthesis and studies of various structures of the adaptive controller were carried out. On the pretext of the conducted studies, the most effective structure of the adaptive control system, which supports the device at the specified temperature level, was proposed.